Examining teachers’ organizational commitment: does teachers’ educational qualification, teaching experience and gender matter? - Gyeltshen, Lotey (Humanities, Arts and Social Sciences Studies, 2021)
Success of any nation depends on how well their education system has been established and how well the nation’s education system is justified through the work of the teachers. Therefore, teachers’ commitment towards their job is regarded as one of the key element in building quality education system in the country. In fact teachers are the key players in the quality education delivery and nation building. So, to examine the teachers’ job commitment towards their organization this study was conducted. Basically this quantitative study tried to answer two research questions; what is the level of organizational commitment of teachers in the higher secondary school of Bhutan? And are there differences in perception of teachers on their organizational commitment level based on gender, educational qualification and teaching experience in the higher secondary schools of Bhutan? The target population identified for the study was the school teachers teaching in different higher secondary schools of Bhutan in the academic year 2018. Self administered survey questionnaire on five point likert scale was distributed to 305 higher secondary school teachers selected through simple random sampling method to collect the required data. The collected data was coded in SPSS to generate the result. The descriptive result analysis revealed that the overall teachers’ level on the organizational commitment at high with statistical differences in teachers’ level on their organizational commitment based on gender. The Independent t-test analysis indicated that females showed little higher commitment level towards their organization than males. However, it was found that there was no relationship between teacher’s educational qualification, teaching experience and organizational commitment of teachers.